Preparation of flavonoids from Amomum tsaoko and evaluation of their antioxidant and α-glucosidase inhibitory activities - Zelin Huang; Yan Zhao; Weixing Yang; Lu Lang; Jun Sheng; Yang Tian; Xiaoyu Gao (Food Chemistry: X)
Amomum tsaoko is an important homologous medicinal and food plant, and its fruit is rich in flavonoids. However, few studies have reported the preparation and bioactivity of flavonoids in A. tsaoko (ATF). In this study, the optimal conditions for ultrasound-assisted extraction of ATF were identified through response surface optimization. HPD300 was identified as the best resin for the purification of ATF, as it exhibited a Freundlich model-conformative adsorption isotherm. Among the different concentrations of ethanol, 20 % and 30 % resulted in higher flavonoid purity (>90 %) and stronger antioxidant and α-glucosidase inhibition activities. A widely targeted metabolomics assay revealed that the relative abundance of flavonoids in a mixture of 20 % and 30 % ethanol eluates was greater than 73 %, which mainly contained (+)-epicatechin, isoquercitrin, astragalin kaempferol-3-O-rutinoside, and procyanidin B2. These findings provide a theoretical basis for the in-depth development and potential use of ATF in the functional food, cosmetic and pharmaceutical industries.